Pengembangan dan Pelatihan Sistem Informasi Digital Sekolah Menengah Kejuruan di Daerah Perbatasan RI - RDTL - Tey Seran, Krisantus J.; Ullu, Hevi Herlina; Blegur, Ernes Josias; Sari, Nila Puspita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
The implementation of ICT has entered the world of Indonesian vocational education, especially in Vocational High Schools. SMK Suarna Wisata Tes, until this training, did not have a centralized and official digital-based information system. The presentation and dissemination of information are still done through several social media platforms, requiring special attention in the management process. Addressing this issue, the Community Service Team of the Information Technology Study Program at the University of Timor developed and conducted training on a digital information system (website) for SMK Suarna Wisata. The main objective of this activity is to assist the school in managing data and information digitally and centrally. The general public can easily access information about the school, teachers, and school activities. The public and the school can communicate through the Suggestions page available on this website. As a result of this Community Service activity, SMK Suarna Tes has a centralized information system management center that the wider community can access. All information about the school is available to the public without needing to visit the SMK Suarna location directly.